Bone Cement Solidifiliation Influence the Limb Alignment and Gap Balance during TKA. (22nd January 2015) - Shi, Dongquan; Xu, Xingquan; Guo, Anyun; Dai, Jin; Xu, Zhihong; Chen, Dongyang; Jiang, Qing
Abstract : Introduction . Mechanical alignment deviation after total knee arthroplasty is a major reason for early loosening of the prosthesis. Achieving optimum cement penetration during fixation of the femoral and tibial component is an essential step in performing a successful total knee arthroplasty. Bone cement is used to solidify the bone and prosthesis. Thickness imbalance of bone cement leads to the deviation of mechanical alignment. To estimate the influence of bone cement, a retrospective study was conducted. Materials and Methods . A total of 36 subjects were studied. All the TKA were performed following the standard surgical protocol for navigated surgery by medial approach with general anaesthesia. Prostheses were fixed by bone cement. Results . We compared the mechanical axis, flexion/extension, and gap balance before and after cementation. All the factors were different compared with those before and after cementation. Internal rotation was reached with statistical significance (P = 0.03 ). Conclusion . Bone cement can influence the mechanical axis, flexion/extension, and gap balance. It also can prompt us to make a change when poor knee kinematics were detected before cementation.